Generation of a Microsporidia Species Attribute Database and Analysis of the Extensive Ecological and Phenotypic Diversity of Microsporidia - Brandon M. Murareanu (American Society for Microbiology, 2021)
Microsporidia are a large group of parasites that cause death and disease in humans and many agriculturally important animal species. To fully understand the diverse properties of these parasites, we curated species reports from the last 160 years.